2022
DOI: 10.1001/jamanetworkopen.2022.11510
|View full text |Cite
|
Sign up to set email alerts
|

Assessment of Latent Subgroups With Suicidal Ideation and Suicidal Behavior Among Gun Owners and Non–Gun Owners in the US

Abstract: IMPORTANCEFirearm ownership is associated with increased risk for suicide. OBJECTIVE To examine patterns of associations among suicidal thoughts and behaviors among gun owners and non-gun owners in the US. DESIGN, SETTING, AND PARTICIPANTS In this survey study, cross-sectional online survey data were collected from March to April 2020 from US adults recruited via Qualtrics Panels. Quota sampling was used to approximate US census demographics. MAIN OUTCOMES AND MEASURESThe primary outcomes were past-year passiv… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
4
0

Year Published

2022
2022
2023
2023

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 10 publications
(4 citation statements)
references
References 35 publications
0
4
0
Order By: Relevance
“…Another consideration in interpreting these findings is that recent research has raised questions regarding the extent to which firearm owners-particularly those at high risk for suicide-feel that typical questions assessing suicidal ideation accurately reflect their lived experience. Specifically, Bryan et al (2022) reported that, in a sample of 10,625 US adults, firearm owners with a higher probability of suicidal behavior were less likely than their peers to endorse suicidal thoughts on the SITBI-R, the same measure utilized in our sample. In the current study, only those endorsing past year or past month suicidal ideation were included and, as such, it is possible that suicidal servicemembers from the larger sample were excluded from the current analyses because the SITBI-R did not accurately capture risk.…”
Section: Discussionmentioning
confidence: 95%
“…Another consideration in interpreting these findings is that recent research has raised questions regarding the extent to which firearm owners-particularly those at high risk for suicide-feel that typical questions assessing suicidal ideation accurately reflect their lived experience. Specifically, Bryan et al (2022) reported that, in a sample of 10,625 US adults, firearm owners with a higher probability of suicidal behavior were less likely than their peers to endorse suicidal thoughts on the SITBI-R, the same measure utilized in our sample. In the current study, only those endorsing past year or past month suicidal ideation were included and, as such, it is possible that suicidal servicemembers from the larger sample were excluded from the current analyses because the SITBI-R did not accurately capture risk.…”
Section: Discussionmentioning
confidence: 95%
“…The results for gender provided some evidence that females may be more likely to disclose suicidal ideation or behaviours to others relative to males. This is an important finding given that males are also more likely to use lethal means when attempting suicide (Bryan et al, 2022). Given that disclosure can be thought of as a coping behaviour and protective factor for death by suicide, this gender effect may help to explain why males more often go on to die by suicide (WHO, 2021).…”
Section: Discussionmentioning
confidence: 99%
“…The fact that elevated suicidal ideation was found among Black firearm owners is an important consideration particularly given that extant literature largely supports that firearm owners are not more likely than nonfirearm owners to experience suicidal ideation (Anestis et al, 2020; Ilgen et al, 2008; Miller et al, 2009). Further, a recent survey of nearly 11,000 U.S. adults revealed that as actual risk of suicide increased (e.g., preparatory behaviors), firearm owners were less likely than nonfirearm owners to endorse suicidal thoughts (Bryan et al, 2022). Recent research has demonstrated that individuals who purchased firearms since March 2020 are more likely to report lifetime, past year, and past month suicidal ideation than are other firearm owners and nonfirearm owners (M. D. Anestis et al, 2021), particularly if the firearm they purchased during this timeframe was their first firearm (Anestis, Bandel et al, 2021).…”
Section: Discussionmentioning
confidence: 99%
“…Thus, causal inferences cannot be made. Furthermore, prior literature (Bryan et al, 2022) notes concerns regarding the ability for screening tools to accurately detect suicide risk, particularly among firearm owners, highlighting a potential limitation of utilizing self-report measures to assess study variables. Although the time point of data collection can be seen as a strength, it did not allow us to determine firearm ownership habits among Black U.S. residents before the COVID-19 pandemic and the media's increased attention of the social justice movement in 2020.…”
Section: Limitations and Conclusionmentioning
confidence: 99%